Early Growth of Soursop (Annona muricata) as Affected by Different Levels of Powerplant Liquid Organic Fertilizer in Abraka, Delta State, Nigeria (Sahel Journal of Life Sciences FUDMA, 2024)
This study was conducted in 2022 and repeated in 2023 to assess the effects of Liquid Organic Fertilizer (LOF) on the early growth of soursop (Annona muricata) in Abraka, Delta State, Nigeria. Five different rates of fertilizer in litres per hectare were applied to the soil-filled poly pots where the seeds were planted according to the treatments – 0, 5, 10, 15 and 20 lha-1. The experiment was carried out in a randomized complete block design with three replications. Six parameters were investigated to achieve the objectives of the study, including initial soil physicochemical properties, germination percentage (%), plant height, number of leaves/plant, leaf area and collar diameter of Annona muricata. The results of the study showed that plants that received 20 lha-1 of LOF were outstanding in all the parameters tested. Based on the findings of the study, it was therefore recommended that farmers adopt LOF application rate of 20 lha-1 for increased growth of Annona muricatain Abraka, Delta State, Nigeria.